Ageing-driven molecular and functional changes in the bovine endometrium - Marine Denis; Doulaye Dembélé; Christophe Richard; Marie Leduc; Maud Pez; Pierrette Reinaud; Olivier Dubois; Hélène Kiefer; Hélène Jammes; Valérie Gelin; Fabienne Constant; François Vialard; et al. (PLoS ONE, 2025)
Understanding how ageing impacts endometrial function is crucial for preserving fertility in older females. While ageing-related cellular dysfunction and inflammation are observed in the bovine uterus, its effects on endometrial physiology remain unclear. Using an experimental model of young (4−7 years) and old (13−15 years) cloned female cattle, we assessed the effect of ageing on the endometrium through transcriptome profiling and responses of cultured endometrial cells to interferon tau (IFNT) and of cultured endometrial explants to LPS. Progesterone profiles were similar between young and old females. Transcriptomic analysis of endometrial biopsies on day 15 of the estrous cycle identified 859 differentially expressed genes (DEG; p ≤ 0.05, |FC| ≥ 1.5), among which 402 DEG were over-expressed and 457 DEG were under-expresssed in old females. These DEG are linked to immune, inflammatory, metabolic, and cell organization pathways and networks. RT-qPCR validation of selected candidate DEG revealed an increased expression of COL4A3, CPA3, IGFBP1, IGFBP2, RSAD2, SCARA5, and SERPINA14 in young females. In vitro stimulation with IFNT of primary uterine glandular epithelial and stromal cells revealed that glandular epithelial cells exhibit a greater sensitivity to IFNT than stromal cells, both in old and young females. Glandular epithelial cells derived from old females exhibit a weaker response to IFNT, in terms of the number of differentially expressed genes, compared to those from young females. The effect of LPS treatment on cytokine concentrations was lightly more pronounced in young females than in old females, with LPS leading to a significant increase in the concentration of IL-1α, IL-1β, IL-6 and IL-10 in young females. By altering the transcriptomic profile of the endometrium and its capacity to respond to both the embryo’s signal and inflammatory factors, we propose that age may be a key factor underlying uterine-related reproductive failures. Further experiments are required to confirm this hypothesis.